STDP STRATEGY ANALYSIS AND E-MARKETING OF ANGEL COLLECTION IN BATAM - Suyono Saputro; Noviani Noviani (Universitas Internasional Batam, 2022)
The purpose of composing this practical work activity aims to develop an E- marketing system and sales strategies by determining segments, target markets, positions, and differentiation which are designed to increase the sales of Angel Collection.This practical work uses interview observation, design, and implementation methods. Designing a system for making social media that is in accordance with the needs of Angel Collection, such as creating a Shopee/Instagram account and collaborating with the necessary resellers. Angel collection have been able to produce Segment, Target Market, Differentiation and Positioning (STDP) and E-Marketing strategies. clear.